2016
DOI: 10.3390/foods5010005
|View full text |Cite
|
Sign up to set email alerts
|

Triticale Bran Alkylresorcinols Enhance Resistance to Oxidative Stress in Mice Fed a High-Fat Diet

Abstract: Triticale (× Triticosecale Whitm.) is a cereal grain with high levels of alkyresorcinols (AR) concentrated in the bran. These phenolic lipids have been shown to reduce or inhibit triglyceride accumulation and protect against oxidation; however, their biological effects have yet to be evaluated in vivo. The purpose of this study was to determine the effects of ARs extracted from triticale bran (TB) added to a high–fat diet on the development of obesity and oxidative stress. CF-1 mice were fed a standard low-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
(52 reference statements)
2
15
0
Order By: Relevance
“…The data of the current study indicated that DLE diminished hepatic steatosis caused by HFD, corresponding with the reduction of liver parameters. Furthermore, HFD-induced obesity is known to cause oxidative damage through lipid peroxidation, the depletion of endogenous antioxidants and the reduction of the activities of antioxidant enzymes, such as SOD, CAT and GPx (19,39,40). In the present study, HFD feeding of mice resulted in oxidative damage as seen by the reduction of the major endogenous antioxidant GSH, the decrease in SOD, CAT and GPx activities, and the induction of lipid peroxidation products.…”
Section: Discussionsupporting
confidence: 48%
“…The data of the current study indicated that DLE diminished hepatic steatosis caused by HFD, corresponding with the reduction of liver parameters. Furthermore, HFD-induced obesity is known to cause oxidative damage through lipid peroxidation, the depletion of endogenous antioxidants and the reduction of the activities of antioxidant enzymes, such as SOD, CAT and GPx (19,39,40). In the present study, HFD feeding of mice resulted in oxidative damage as seen by the reduction of the major endogenous antioxidant GSH, the decrease in SOD, CAT and GPx activities, and the induction of lipid peroxidation products.…”
Section: Discussionsupporting
confidence: 48%
“…Oxidative stress, caused by reactive oxygen species (ROS), is responsible for modulating several pathological conditions in CVD, T2D, obesity and inflammation (Agil et al, 2016;Vinderola et al, 2006;Vuong et al, 2010). Consumption of food containing bioactives showed to decrease the risk of chronic diseases and these health benefits might be attributed to the antioxidant capacity of phytochemicals in foods (Dinu et al, 2017;Zhu et al, 2017).…”
Section: Diet and Prevention Of Oxidative Stressmentioning
confidence: 99%
“…Invitro studies have shown that bioactives in foods such as pheno-lics, dietary fibre and peptides have the ability to scavenge ROS (Agil et al, 2012;Chandrasekara et al, 2011;Gliwa et al, 2011;Yeo et al, 2015). Thus, it is crucial to find the relationship between the chemical structure of plant bioactives and their functionality in food and biological systems (Agil et al, 2013;Agil et al, 2016;Ainsley Reid et al, 2005;Ajibola et al, 2011;Al-Farsi et al, 2005;Chandrasekara et al, 2011;Gunenc et al, 2017). In plants, phenolics/polyphenols compounds can be divided into free, esterified and insoluble-bound forms.…”
Section: Diet and Prevention Of Oxidative Stressmentioning
confidence: 99%
“…These components include: specific proteins, starches, b-glucan, pentosans, fibre (soluble and insoluble) and tocols. Moreover, the levels of dietary fibre and lignans in triticale may be high enough for use in high fibre food products, which are beneficial for human health (Hosseinian et al, 2009;Rakha et al, 2011;Nakurte et al, 2012;Agil et al, 2014;Agil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%